1994
DOI: 10.1089/hyb.1994.13.423
|View full text |Cite
|
Sign up to set email alerts
|

A Kringle-Specific Monoclonal Antibody

Abstract: Kringle domains are found in several plasma proteins of blood coagulation and fibrinolysis. A murine monoclonal antibody, designated alpha HII-5, was produced against a synthetic peptide representing residues 216-231 of human prothrombin kringle 2. The sequence of the hexadecapeptide (Glu-Asn-Phe-Cys-Arg-Asn-Pro-Asp-Gly-Asp-Glu-Glu-Gly-Val-Gly-Cys) is conserved in several kringle-containing proteins, represents a predicted region of high local hydrophilicity in prothrombin kringle 2, and contains the anionic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…1,16 There are also other reports supporting the concept of cross-reactive antikringle antibodies. Church and his group 18 immunised mice with a synthetic peptide from prothrombin kringle 2 containing a highly conserved region of the kringle proteins, and showed that a monoclonal antibody to this peptide recognised plasminogen kringle 5 in solid phase, not in liquid phase. The same monoclonal antibody bound other kringle proteins t-PA, apo(a), prothrombin and intact plasminogen in the solid phase.…”
Section: Discussionmentioning
confidence: 99%
“…1,16 There are also other reports supporting the concept of cross-reactive antikringle antibodies. Church and his group 18 immunised mice with a synthetic peptide from prothrombin kringle 2 containing a highly conserved region of the kringle proteins, and showed that a monoclonal antibody to this peptide recognised plasminogen kringle 5 in solid phase, not in liquid phase. The same monoclonal antibody bound other kringle proteins t-PA, apo(a), prothrombin and intact plasminogen in the solid phase.…”
Section: Discussionmentioning
confidence: 99%
“…Church et al (1994 ) have shown that monoclonal antibodies raised against the kringle 2 of prothrombin also recognize the kringle 5 of plasminogen, but not the other four kringle units. In our preliminary experiments we found that antiprothrombin antibodies were not inhibited by preparations of plasminogen containing either kringles 1–3 or 4, but did react with the whole molecule (data not shown).…”
Section: Discussionmentioning
confidence: 99%